Synthesis of silver nanoparticles doped in the zeolite framework by chemical reduction method - Hien, Nguyen Quoc; Ai Trinh, Nguyen Thuy; Phu, Dang Van; Duy, Nguyen Ngoc; Quoc, Le Anh (Vietnam Journal of Science and Technology, 2015)
ABSTRACT Silver ions (Ag+) were introduced at first into the porous zeolite 4A lattice by an ion-exchange route. And then silver nanoparticles (AgNPs) were synthesized in the zeolite framework by chemical reduction method using hydrazine hydrate (N2H4. H2O) as reducing agent. The synthesized AgNPs/zeolite product was characterized by ultraviolet-visible spectroscopy (UV-vis), X-ray diffraction (XRD), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). The results showed the maximum absorption wavelength (lmax) of AgNPs/zeolite at 427 nm and the average size of the metallic AgNPs doped in the zeolite of about 30 nm. The synthesis process has been considered as suitable one to prepare AgNPs/zeolite with AgNPs content in zeolite of about 1.2% on large scale. The obtained AgNPs/zeolite product has been used for production of porous ceramic water filters with efficiently bacterial disinfection effect for treatment of drinking water.